Pelatihan Manajemen Kas Bagi Pelaku Usaha Mikro dan Kecil di Kelurahan Kandang Limun Kecamatan Muara Bangkahulu Kota Bengkulu - Abdullah Abdullah; Fadli Fadli; Lizar Imanjaya; Muhammad Limas Carrow (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2023)
Cash management training is provided for business owners in the Kandang Limun Village, Muara Bangkahulu Sub-district, Bengkulu City. This activity is carried out to foster a spirit of productivity in running their businesses. It also serves as an opportunity to prevent loss of income and business opportunities that they have had so far. The business community in Kandang Limun Village, Muara Bangkahulu Sub-district, Bengkulu City, has a strong desire to improve their businesses, both in terms of funding and basic family needs. However, their desires are not accompanied by the ability to manage their finances. In order to realize organized and optimal cash utilization, cash management training is provided for Micro, Small, and Medium Enterprises (MSMEs) in Kandang Limun Village, Muara Bangkahulu Sub-district, Bengkulu City. Through this service activity, MSME entrepreneurs are equipped with knowledge and procedures for cash management. With the skills and abilities acquired, entrepreneurs can enhance productivity in their businesses. This service activity is conducted through lecture/demonstration and discussion (question and answer) methods. The training aims to stimulate responses from business players. The cash management training activity will be implemented with intensive mentoring and active involvement from the academic community of Bengkulu University.